India’s Kashmir Conundrum: A Strive after Burhan Wani Demise and Implementation of Article 370 - Farzana Zaheer Syed; Asia Saif Alvi; Sultan Mubariz (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Kashmir, a beautiful valley in northern Pakistan, has been a source of contention between India and Pakistan for many decades. The Kashmiri freedom fighters’ unwavering commitment to the right to self-determination has fuelled the two countries’ efforts (Pakistan and IOJK) to seek long-term peace in the region through the liberation of the Kashmiris from Indian aggression. This paper focuses on the Kashmiris’ never-ending freedom struggle, particularly in light of the murder of Burhan Wani and its ramifications for Pakistan-India relations, which are already strained. The Indian government imposed Article 370 in order to consult credible secondary data, books, journals, research articles, and renowned magazines. Pakistan has long sought an empirically peaceful solution to the region’s nuclear threat. It is high time for both neighbouring countries to maintain the Composite Dialogue Process and engage in diplomatic efforts to bring this conflict to a lasting and peaceful conclusion.